Q: What is a 2 step equation that equals 7?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Slope for the equation y equals 7 is zero.

It is an equation and the value of g is 2.

7

im assuming your equation is 2x + 1 = 7 in this case you need to find what x equals 2x + 1 = 7 2x + 1 - 1 = 7-1 2x = 6 x = 3 put it back into the equation to check if your answer is correct 2(3) + 1 = 7 6 + 1 = 7 7 = 7 Correct! if your equation is 2x - 1 = 7 x = 4 check it 2(4) - 1 = 7 8 - 1 = 7 7 = 7 Correct! if your equation is 2x1 = 7 x = 7/2 check it 2(7/2)1 = 7 2(7/2) = 7 2 * 7 / 2 = 7 14/2 = 7 7 = 7 Correct! hope i got your equation right. if not you can message me on my message board to get more help.

Now simplify the equation by doing the math. 2−2+x=7−2

Related questions

2+2+2+2+2-7 This is an equation that uses 5 2's yet equals 3.

When you are solving a 2-step equation, you do the opposite of a 1-step equation. You do addition and subtraction first, then the multiplication second. Example: 2x + 9=16 -9 -9 2x=7 Now it's a 1-step equation 2x=7 /2 /2 Your answer would be 3.5 To check all you do is replace the variable with your answer. 2x + 9=16 2(3.5) + 9=16

Slope for the equation y equals 7 is zero.

7

x=2/7

It is an equation. Taking it step by step: 17 = 3t - 4 17 + 4 = 3t 21 = 3t 7 = t So the value of t is 7.

7

It is an equation and the value of g is 2.

im assuming your equation is 2x + 1 = 7 in this case you need to find what x equals 2x + 1 = 7 2x + 1 - 1 = 7-1 2x = 6 x = 3 put it back into the equation to check if your answer is correct 2(3) + 1 = 7 6 + 1 = 7 7 = 7 Correct! if your equation is 2x - 1 = 7 x = 4 check it 2(4) - 1 = 7 8 - 1 = 7 7 = 7 Correct! if your equation is 2x1 = 7 x = 7/2 check it 2(7/2)1 = 7 2(7/2) = 7 2 * 7 / 2 = 7 14/2 = 7 7 = 7 Correct! hope i got your equation right. if not you can message me on my message board to get more help.

there are infinite equations. 7-1-1-1-1-1-1, 8-2-1-1-1-1-1, ...

(\frac{1}{z})^{min(\frac{x-2\sqrt{xy}+y}{2})} = 1

If the equation is (5x + 3 - 7) / 2 = 56, than x = 23.2